2013
DOI: 10.1590/s0004-28032013000100010
|View full text |Cite
|
Sign up to set email alerts
|

Early Complications in Bariatric Surgery:

Abstract: -Context -Bariatric surgery has proven to be the most effective method of treating severe obesity. Nevertheless, the acceptance of bariatric surgery is still questioned. The surgical complications observed in the early postoperative period following surgeries performed to treat severe obesity are similar to those associated with other major surgeries of the gastrointestinal tract. However, given the more frequent occurrence of medical comorbidities, these patients require special attention in the early postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 16 publications
(22 reference statements)
1
17
0
3
Order By: Relevance
“…Considering the entire period of study, mortality from causes related to surgery was 1.0% and from violent death was 0.3%. Early mortality rate was similar to that observed in other studies of patients who underwent the same surgical procedure (21-23). Some studies reported higher mortality rates such as 0.9% (5), 1.9% (8), 3.7% (11), and 4.1% (12), but they included patients operated on much earlier, from 1980 to the early 2000s, when surgical conditions were probably less developed than today (5,8).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Considering the entire period of study, mortality from causes related to surgery was 1.0% and from violent death was 0.3%. Early mortality rate was similar to that observed in other studies of patients who underwent the same surgical procedure (21-23). Some studies reported higher mortality rates such as 0.9% (5), 1.9% (8), 3.7% (11), and 4.1% (12), but they included patients operated on much earlier, from 1980 to the early 2000s, when surgical conditions were probably less developed than today (5,8).…”
Section: Discussionsupporting
confidence: 88%
“…Male gender has been associated with lower survival rates after bariatric procedure in several studies (6,7,21), when analyzing all causes of death. This may be explained by factors not related to the bariatric surgery itself.…”
Section: Discussionmentioning
confidence: 99%
“…By retrospectively analyzing major complications (fistula, cavitary abscess, bleeding and deep wound infection) and mortality in the group of patients (n = 538) operated on before the beginning of this protocol ( 17 ) and by stratifying this group by BMI, we noted that the BMI >50 kg/m 2 group had a greater incidence of all major complications and represented the patient group with the majority of complications in our series. The fistula rate was 2.19% for all the patients (non-SO and SO), and the subgroup analysis revealed a 1% fistula rate in the non-SO group (n = 345), representing 30.76% of the total number of fistulas.…”
Section: Discussionmentioning
confidence: 97%
“…In a retrospective analysis of the data from patients operated on five years prior to the start of the preoperative weight loss program, we found that the incidence of complications in SO patients was approximately 4-fold higher compared with morbidly obese group (BMI<50 kg/m 2 ), and that 80% of the deaths occurred in super obese ( 17 ).…”
Section: Introductionmentioning
confidence: 93%
“…88 Early complication rates (< 30 days) after bariatric surgery were reported to be < 10% 73,94 and tended to be lower in restrictive surgeries compared with in hybrid surgeries. 50,73 Most common early complications reported are gastric and anastomosis leak (1.6% to 5.1%), 73,95,96 bleeding (0.5% to 3.5%), 50,73,97 and pulmonary embolism (0.2% to 1.0%).…”
Section: Mortalitymentioning
confidence: 99%